The value of SPARCC sacroiliac MRI scoring in axial psoriatic arthritis and its association with other disease parameters - GEZER, HALİSE HANDE; DURUÖZ, MEHMET TUNCAY (My University, 2022)
Objectives This study aimed to assess patients with axial psoriatic arthritis (AxPsA) using the Canadian Spondyloarthritis Research Consortium (SPARCC) sacroiliac joint (SIJ) scores and to seek correlations between magnetic resonance imaging (MRI) scores and disease characteristics. Methods Forty PsA patients (32 females, mean age 46.4 years) who had been documented to have active or structural lesions on SIJ MRI were retrospectively evaluated. Disease duration, medications, and disease activity, including Disease Activity in Psoriatic Arthritis (DAPSA), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), minimal disease activity (MDA), and Ankylosing Spondylitis Disease Activity Score (ASDAS) were recorded. On sacroiliac MRI scans, the SPARCC scores of sacroiliac joint inflammation (SIS) and sacroiliac joint structural damage (SSS) were evaluated. Results The mean disease duration was 51.4 +/- 70.4 months. MRI showed active inflammation in 30 patients (75%) and at least 1 structural lesion in 32 patients (92.5%). The most prevalent structural lesion was erosion (82.5%), followed by fat metaplasia (65%), backfill (12.5%), and ankylosis (2.5%). Only fat metaplasia scores were significantly higher in men than in women (P = .007). Of clinical and laboratory parameters, only C-reactive protein (CRP) was significantly higher in the presence of active inflammation (P = .01). The SIS score was significantly correlated with disease duration (r = -.35) and CRP levels (r = .42,). The SSS score was inversely correlated with BASDAI (r = -.37), ASDAS-CRP (r = -.39), and ASDAS - erythrocyte sedimentation rate (r = -.32). The overall SPARCC scores did not differ between patients in DAPSA remission and non-remission and between those in MDA and non-MDA. Conclusion Although radiologic involvement is generally not severe in AxPsA, MRI still provides additional information about inflammatory activity and structural lesions. CRP may be helpful in monitoring the radiologic disease activity in AxPsA.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Rheumatology; disease activity; inflammation; MRI; psoriatic arthritis; structural damage; SPONDYLOARTHRITIS RESEARCH CONSORTIUM; ANKYLOSING-SPONDYLITIS; ACTIVITY INDEX; INFLAMMATION; VALIDATION